PENGARUH DISIPLIN KERJA DAN LOYALITAS TERHADAP PRESTASI KERJA PEGAWAI PADA KANTOR KECAMATAN TUHEMBERUA KABUPATEN NIAS UTARA - Zega, Yamolala (Smart Education, 2025)
Abstract: From the results of partial testing (t-test) of the work discipline variable (X1) on the work performance variable (Y) and based on the T-test criteria, a significance of 0.221> 0.05 was obtained and the calculated t value = 1.246 <t table = 2.024, then Ho is accepted, it can be concluded partially that there is no influence of work discipline on work performance at the Tuhemberua District Office, North Nias Regency. From the results of partial testing (t-test) of the loyalty variable (X2) on the work performance variable (Y) and based on the T-test criteria, a significance of 0.00> 0.05 was obtained and the calculated t value = 5.575> t table = 2.024, then Ho is rejected, it can be concluded partially that there is an influence of loyalty on work performance at the Tuhemberua District Office, North Nias Regency. From the results of data processing, the significance value is 0.0 which is smaller than 0.05. From this analysis, Ho is rejected, meaning that there are independent variables simultaneously affecting the dependent variable. To improve employee work performance, employee discipline and employee loyalty must also be improved. Keywords: Discipline, Loyalty, Tuhemberua District Office, North Nias Regency, Work performance Abstrak: Dari hasil pengujian parsial (Uji t) variabel disiplin kerja (X1) terhadap variabel prestasi kerja (Y) dan berdasarkan kriteria Uji T, didapatkan signifikansi sebesar 0,221> 0,05 dan nilai t hitung = 1,246 < t tabel = 2,024, maka Ho diterima, dapat disimpulkan secara parsial bahwa tidak terdapat pengaruh disiplin kerja terhadap prestasi kerja pada Kantor Kecamatan Tuhemberua Kabupaten Nias Utara. Dari hasil pengujian parsial (Uji t) variabel loyalitas (X2) terhadap variabel prestasi kerja (Y) dan berdasarkan kriteria Uji T, didapatkan signifikansi sebesar 0,00> 0,05 dan nilai t hitung = 5,575 > t tabel = 2,024, maka Ho ditolak, dapat disimpulkan secara parsial bahwa terdapat pengaruh loyalitas terhadap prestasi kerja pada Kantor Kecamatan Tuhemberua Kabupaten Nias Utara. Dari hasil pengolahan data, didapatkan nilai signifikansi adalah sebesar 0,0 yang lebih kecil daripada 0,05. Dari analisis tersebut, maka Ho ditolak, artinya ada secara simultan variabel bebas mempengaruhi variabel terikat. Untuk meningkatkan prestasi kerja pegawai, maka harus ditingkatkan pula kedisiplinan pegawai dan loyalitas pegawai. Kata kunci: Kedisiplinan, Loyaloitas, Kantor Kecamatan Tuhemberua Kabupaten Nias Utara, Prestasi kerja